2021
DOI: 10.21203/rs.3.rs-148982/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depth-dependent Influence of Biochar Application on the Abundance and Community Structure of Diazotrophic Under Sugarcane Growth

Abstract: Despite progress in understanding diazotrophic distribution in surface soils, few studies have investigated the distribution of diazotrophic in dipper soil layers. Here, we leveraged high-throughput sequencing (HTS) of nifH genes obtained to assess the influence of biochar amended soil (BC) and control (CK), and soil depths (0-20, 20-40 and 40-60 cm) on diazotrophic abundance and community structures, and soil biochemical properties. Although soil physio-chemical properties, enzymes activities, diazotrophic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Studies have shed light on the decline in ratoon crop growth, development, and productivity, mainly due to nutrient depletion and pest and disease outbreaks (Xu et al, 2021;Fallah et al, 2023). We recently reported that BC was key in rejuvenating ratoon crop traits (Fallah et al, 2023). Here, ratoon crop traits under the sustained effect of BC and FM-supplemented soils peaked significantly, largely due to the regulatory effects of these amendments on pathogenic bacteria and stress-regulating metabolites, which draws parallels with previous findings (Gomathi, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Studies have shed light on the decline in ratoon crop growth, development, and productivity, mainly due to nutrient depletion and pest and disease outbreaks (Xu et al, 2021;Fallah et al, 2023). We recently reported that BC was key in rejuvenating ratoon crop traits (Fallah et al, 2023). Here, ratoon crop traits under the sustained effect of BC and FM-supplemented soils peaked significantly, largely due to the regulatory effects of these amendments on pathogenic bacteria and stress-regulating metabolites, which draws parallels with previous findings (Gomathi, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Studies have shed light on the decline in ratoon crop growth, development, and productivity, mainly due to nutrient depletion and pest and disease outbreaks (Xu et al, 2021;Fallah et al, 2023). We recently reported that BC was key in rejuvenating ratoon crop traits (Fallah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugarcane stalks were cut approximately 10-12 cm in length, maintaining two buds on each set. Subsequently, 10 sets were planted in each row, ensuring a spacing of 0.3 m between plants and 0.5 m between rows (Fallah et al, 2021). We supplemented the BC and CK treatments with 375 kg/hm 2 of compound fertilizer (N-P 2 O 5 -K 2 O 15-15-15) in April 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of cane agronomic traits, namely, sugarcane heights, sucrose content, and stalk weight (kg stalk −1 ), followed by the theoretical production and yield parameters, was conducted in November 2019 using the method we adopted in our previous studies (Fallah et al, 2021;Pang et al, 2022).…”
Section: Measurement Of Sugarcane Agronomic Traitsmentioning
confidence: 99%